Pion pT Spectra in p+p Collisions as a Function of s and Event Multiplicity - Priyanka Sett; Prashant Shukla (Advances in High Energy Physics)
We study the charged pion transverse momentum (pT) spectra in p+p collisions as a function of collision energy s and event multiplicity using Tsallis distribution. This study gives an insight of the pion production process in p+p collisions. The study covers pion spectra measured in p+p collisions at SPS energies (6.27–17.27 GeV), RHIC energies (62.4 GeV and 200 GeV), and LHC energies (900 GeV, 2.76 TeV, and 7 TeV). The Tsallis parameters have been obtained and parameterized as a function of s. The study suggests that as we move to higher energy more and more hard processes contribute to the spectra. We also study the charged pion spectra for different event multiplicities in p+p collisions for LHC energies using Tsallis distribution. The variation of the Tsallis parameters as a function of event multiplicity has been obtained and their behavior is found to be independent of collision energy.